CORRUPTION AND REVERSAL BURDEN OF PROOF - Wiriadinata, Wahyu (UI Scholars Hub, 2015)
This paper, entitled Corruption and Reversal Burden of Proof, was intended to deal with a question on the extent of the effectiveness of a reversal burden of proof as stipulated in positive (applicable) Indonesia law, that is, as provided for in Law Number 31 of 1999 on Eradication of Corruption Crime. Then, a problem that rose next was: could the application of reversal burden of proof in proving a corruption crime case prevent or reduce or even eliminate totally corruption crimes in Indonesia? This research built on a theoretical frame of thought from Roscoe Pound, who maintains that law is a tool of social engineering. This concept was cited by Muchtar Kusumaatmadja, who adapted it to Indonesia conditions and adjusted it to be law as a social engineering medium. Engineering is meant here as a transformation of the thinking ways of people from traditional thinking ways to modern ones. Law should be made as a means in resolving the entire problems that emerge between and among community, including corruption crimes. One of the things that needs to be changed is a law of proof law system, that is, from a conventional proof system to be a reversal one. This paper was written by a juridical-normative method, that is, by studying legislations, be they are contained in laws and those contained in literature/books on legal science, particularly legislations related to reversal burden of proof. Then, the results, in a form of juridical aspect, was written in a descriptiveanalytical form. The overall conclusion of this research was an answer of the problems posed above, that is: Corruption crimes have been continuously occurring till now in Indonesia. Thus, Law Number 31 of 1999, particularly Article 37, has not been effective yet in eradicating corruption crimes.